Survey Smoothly Fiber-Wireless (FiWi) Accessing Wireless Networks: Convergence and Challenges - Naseer Hwaidi Alkhazaali; Raed Abduljabbar Aljiznawi; Dheyaa Jasim Kadhim (Institute of Advanced Engineering and Science, 2016)
Traditionally, wireless networks and optical fiber Networks are independent of each other. Wireless networks are designed to meet specific service requirements, while dealing with weak physical transmission, and maximize system resources to ensure cost effectiveness and satisfaction for the end user. In optical fiber networks, on the other hand, search efforts instead concentrated on simple low-cost, future-proofness against inheritance and high services and applications through optical transparency. The ultimate goal of providing access to information when needed, was considered significantly. Whatever form it is required, not only increases the requirement sees technology convergence of wireless and optical networks but also played an important role in future communication networks. Some technical development of wireless access networks-optical and seamless coexistence of both techniques, this paper is a review of the State of the latest developments and advances in optical and wireless communications, major technical challenges to provide flawless communication in fiber- wireless (FiWi) access networks, places of interest important research issues to provide intelligence information, access and transport and the convergence of these networks in the future.